Borrow Cheap, Buy High? The Determinants of Leverage and Pricing in Buyouts - AXELSON, ULF; JENKINSON, TIM; STRÖMBERG, PER; WEISBACH, MICHAEL S. (Journal of Finance, 2013)
ABSTRACT Private equity funds pay particular attention to capital structure when executing leveraged buyouts, creating an interesting setting for examining capital structure theories. Using a large, international sample of buyouts from 1980 to 2008, we find that buyout leverage is unrelated to the cross‐sectional factors, suggested by traditional capital structure theories, that drive public firm leverage. Instead, variation in economy‐wide credit conditions is the main determinant of leverage in buyouts. Higher deal leverage is associated with higher transaction prices and lower buyout fund returns, suggesting that acquirers overpay when access to credit is easier.